2004
DOI: 10.1021/la047994h
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of Enzymes Adsorbed onto Single-Walled Carbon Nanotubes

Abstract: We have examined the structure and function of two enzymes, alpha-chymotrypsin (CT) and soybean peroxidase (SBP), adsorbed onto single-walled carbon nanotubes (SWNTs). SBP retained up to 30% of its native activity upon adsorption, while the adsorbed CT retained only 1% of its native activity. Analysis of the secondary structure of the proteins via FT-IR spectroscopy revealed that both enzymes undergo structural changes upon adsorption, with substantial secondary structural perturbation observed for CT. Consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
437
1
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 483 publications
(462 citation statements)
references
References 30 publications
18
437
1
6
Order By: Relevance
“…They demonstrated that a strong π -π interaction existed between the individual hexagonal cells of the GO basal planes and the glucose oxidase. This is similar to the interactions between the protein molecules and CNTs where the π -π stacking interaction is a dominated factor [112,120] . Apparently, the enzyme immobilization onto GO might be a result of the synergic effect of the different interactions.…”
Section: Noncovalent Adsorption Of the Protein/ Enzyme Molecules On Tsupporting
confidence: 56%
“…They demonstrated that a strong π -π interaction existed between the individual hexagonal cells of the GO basal planes and the glucose oxidase. This is similar to the interactions between the protein molecules and CNTs where the π -π stacking interaction is a dominated factor [112,120] . Apparently, the enzyme immobilization onto GO might be a result of the synergic effect of the different interactions.…”
Section: Noncovalent Adsorption Of the Protein/ Enzyme Molecules On Tsupporting
confidence: 56%
“…Experimental measurements of the thermodynamics of protein folding have been performed primarily in bulk water (41). Although many experiments have probed how interfaces affect protein folding, structure, and function (29,42), to the best of our knowledge, there are no temperature-dependent thermodynamic measurements of self-assembly at interfaces. Extensions of atomic force microscope experiments of pulling a hydrophobic polymer attached to a surface (43) have the potential to quantify the thermodynamics of hydrophobic interactions in interfacial environments described here.…”
Section: Modelsmentioning
confidence: 99%
“…80 An alternative bioconjugation strategy that offers more control over protein orientation while circumventing the structural perturbation caused by direct adsorption is the hybrid noncovalent/covalent approach (Figure 1b, c). In one approach, the SWCNT is noncovalently covered by a synthetic or biological polymer that is covalently conjugated to the protein (Figure 1b).…”
Section: Hybrid Approach: Covalent Attachment Tomentioning
confidence: 99%
“…80,100 The fewer degrees of freedom available to an adsorbed protein, combined with suboptimal orientation or adsorption-induced conformational alterations, may result in loss of protein specificity or activity. 80 The use of natural membrane fragments for suspending SWCNTs offers a much more direct approach to immobilizing membrane proteins, circumventing the need to reconstitute a synthetic membrane and benefiting from an inherent protein environment that has been optimized by nature. However, as is the case with purified protein adsorption, one drawback of using natural membrane fragments is the heterogeneity of nonspecifically adsorbed complexes and nonuniform protein distribution.…”
Section: Engineering Rules For Biomolecule-swcntmentioning
confidence: 99%